Bolsa Família e desigualdade da renda domiciliar entre 2006 e 2011 - Carvalho, Cleusení Hermelina de (2013)
The programs of conditional cash transfer are increasingly playing an important role in combating poverty in many countries of Latin America, especially in Brazil. The objective of this work is to analyze the contribution of Bolsa Família in household income inequality in Brazil between 2006 and 2011. To achieve the purpose, we analyze the relative participation of eight sources of income: labor, pensions, Bolsa Família (proxy variable), pensions, allowances, grants, rents and interest in the five geographical regions, North, Northeast, Midwest, Southeast, and South and metropolitan regions. That said, this study was organized in three chapters. The first chapter presents a reinterpretation of the causes of income inequality backed in Brazilian literature. The second analyzes the income transfer programs in four Latin American countries: Mexico, Chile, Argentina and Peru. The third presents a mathematical technique used to decompose the Gini, we analyze the empirical results for Brazil, macro-regions and metropolitan areas. Finally, it is concluded that, among the presented results, the importance of the Bolsa Família and especially labor income to reduce the degree of inequality